Synthesis and Characterisation of Lanthanide Mixed Complexes Using Benzoin-α-Oxime Thiourea and Phenylthioureas as Ligands. - C. CHAVAN, M.; D. DESHPANDE , V.; Vaidya, P.V. (Asian Journal of Chemistry, 2010)
Mixed ligand complexes of rare earth ions La3+, Pr3+, Nd3+, Sm3+, Gd3+ and Dy3+ with benzoin-α-oxime (cupron) as primary ligand and thiourea, N-phenylthiourea and N,N´-diphenylthiourea as secondary ligands have been synthesied and characterised on the basis of their elemental analysis, electronic and IR spectral data, thermal analysis and conductivity measurements. These studies indicate that there is a strong interaction between lanthanides and the ligands.